Determining therate of diyatthrough the use of gold and silver: an analytical study - Muhammad Husni, Ahmad; Omar, Anwar Fakhri; Alias, Muhammad Nazir; Samuri, Mohd Al-Adib; Che Omar, Nurhayati (American-Eurasian Network for Scientific Information Publications(AENSI), 2013)
Diyat has for long been a topic of discussion among scholars of old and continues to be so to the present day in which it involves gold and silver. These scholars have provided guidelines for determining the diyatrate for gold and silver based on the hadith of the Prophet S.A.W., which includes crimes that cause injuries of the body or death. However, there are some disagreements in determining the rate and type of diyat.This article uses several sources and references such as articles and books as the basis for study. Our analysis shows that though these scholars have different opinions, they also agree that Islamic law lays down many conditions that must be met in the criminal matters, such as the payment of diyat, in order to protect universal justice. The objective of this article is to determine the extent of the use of gold and silver in diyat payment as well as the most accurate evaluation rate. Through this research, an exposure on the payment of diyat through the use of gold will be provided in detail for the knowledge of the general public.